Cross‐species chimeras reveal BamA POTRA and β‐barrel domains must be fine‐tuned for efficient OMP insertion. Issue 4 (6th June 2015) - Browning, Douglas F.; Bavro, Vassiliy N.; Mason, Jessica L.; Sevastsyanovich, Yanina R.; Rossiter, Amanda E.; Jeeves, Mark; Wells, Timothy J.; Knowles, Timothy J.; Cunningham, Adam F.; Donald, James W.; Palmer, Tracy; Overduin, Michael; et al.
Summary BAM is a conserved molecular machine, the central component of which is BamA. Orthologues of BamA are found in all Gram‐negative bacteria, chloroplasts and mitochondria where it is required for the folding and insertion of β‐barrel containing integral outer membrane proteins (OMPs) into the outer membrane. BamA binds unfolded β‐barrel precursors via the five polypeptide transport‐associated (POTRA) domains at its N‐terminus. The C‐terminus of BamA folds into a β‐barrel domain, which tethers BamA to the outer membrane and is involved in OMP insertion. BamA orthologues are found in all Gram‐negative bacteria and appear to function in a species‐specific manner. Here we investigate the nature of this species‐specificity by examining whether chimeric Escherichia coli BamA fusion proteins, carrying either the β‐barrel or POTRA domains from various BamA orthologues, can functionally replace E. coli BamA. We demonstrate that the β‐barrel domains of many BamA orthologues are functionally interchangeable. We show that defects in the orthologous POTRA domains can be rescued by compensatory mutations within the β‐barrel. These data reveal that the POTRA and barrel domains must be precisely aligned to ensure efficient OMP insertion.